Misunderstandings due to cultural differences : two Filipino mothers experiences with the Icelandic educational system - Agnes Renegado 1989- (2016)
Abstract The present research study examines two Filipino mothers´ perspectives related to disciplining their children based on experiences with two different Icelandic school social workers. Due to apparent cultural differences, misunderstandings occurred, leading to a conflict situation regarding how both parties viewed the proper way to handle each child’s perceived behavioural issues in school. This qualitative study focuses the effects of the influence of the students mother’s cultural background with regards to his attitude when he is already in another school environment. The respondents are two Filipino mothers with 8 to 13 year-old children, both of whom have migrated in Iceland from the Philippines. Open ended, in-depth interviews were used to obtain data regarding the respondents’ views and insights. The interviews pointed out the Filipino mothers´ feelings towards their personal encounter with the school social workers regarding the perceived behavioural problems of their children in school. This research study aims at providing a better understanding of the need for greater parental cooperation in diagnosing and solving behavioural problems of children in school so that both parents and the school will work more closely to determine more effective actions or solutions to the problems of foreign transferee students face.